The Libyan press and its role in the growth of national sentiment and its exposure of Italian ambitions in Libya 1910 - 1911 AD (Journal of Human Sciences, 2023)
In this research, we discuss the media campaign that Libya witnessed at the end of the second Ottoman era by the Libyan newspapers and the media campaign that they adopted in order to educate the Libyans about the dangers facing their country represented in the Italian ambitions, and the policy of peaceful penetration followed by the Italian government, and this campaign included all the different groups of the people Whether in the cities, among the educated or the workers, or among the tribesmen and the heads of the Sufi orders in the interior.The Libyan newspapers exposed Italian ambitions in Libya (1910 - 1911 AD), published all its plans on their pages, and alerted the Libyans to the means used by the Italian government in order to implement its colonial plans in the country. It also took upon itself to publish articles published in Italian newspapers after Translated and republished in Arabic, in order for the Libyans to know what the Italians are planning in secret against their country. The Libyan press played a major role in raising awareness and awakening the national spirit and a sense of responsibility among a large number of Libyans, and their dignitaries, whose image became clear through the role played by Libya’s representatives in The Council of Envoys in the Ottoman capital, which was represented in their follow-up to the media campaign led by the Libyan newspapers and what they published on their pages against the Italian danger threatening the country, and their follow-up also to the popular demands in the central government departments in Istanbul. The press also succeeded in its awareness campaign about the dangers of Italian colonial penetration, and this was reflected in the people’s demonstrations of telegraphic protest to the Ottoman Sultan and objecting to the Ottoman appeasement policy towards the expected Italian danger.